Bucco-Adhesive Film as a Pediatric Proper Dosage Form for Systemic Delivery of Propranolol Hydrochloride: In-vitro and in-vivo Evaluation - Mohamad SA; Salem H; Yassin HA; Mansour HF (Dove Medical Press, 2020)
Soad A Mohamad,1 Hesham Salem,2 Heba A Yassin,3 Heba F Mansour4 1Department of Pharmaceutics, Faculty of Pharmacy, Deraya University, Minia, Egypt; 2Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Deraya University, Minia, Egypt; 3Department of Pharmaceutics, Faculty of Pharmacy, Egyptian Russian University, Badr City, Cairo, Egypt; 4Department of Pharmaceutics, Faculty of Pharmacy, Minia University, Minia, EgyptCorrespondence: Heba F MansourDepartment of Pharmaceutics, Faculty of Pharmacy, Minia University, Minia 61111, EgyptEmail heba_mansour@mu.edu.egObjective: To formulate and assess bucco-adhesive films of propranolol hydrochloride for pediatric use.Methods: Different films were formulated adopting mucin, polyvinyl alcohol, chitosan and carbopol. A drug/polymer compatibility study was conducted adopting differential scanning calorimetry and Fourier transform infrared spectroscopy. The prepared films were physically investigated for variation of weight, propranolol content, thickness, surface pH, proportion of moisture, folding endurance and mucoadhesion. In vitro drug release study and kinetic analysis of the corresponding data have been conducted. The optimized formulation was selected for a bioavailability study using albino rabbits and adopting a developed HPLC method. The pharmacokinetic parameters of the drug were calculated following administration of the optimized film and the corresponding marketed oral tablets to albino rabbits.Key Finding: The compatibility study revealed the absence of drug/polymer interaction. The film formulations had suitable mucoadhesive and mechanical properties. The optimized formulation exhibited reasonable drug release that followed Higuchi diffusion pattern. The calculated AUC0-8h presented an enhancement in the bioavailability of propranolol hydrochloride from the selected film formulation by 1.9 times relative to the marketed propranolol oral tablets.Conclusion: These findings support that propranolol hydrochloride bucco-adhesive film can be considered as a proper effective dosage form for pediatric delivery.Keywords: propranolol, buccoadhesive, mucin, film, pediatric, HPLC